Education for refugees: Examining access to basic education in Dadaab Refugee Camps of Ifo, Hagadera, and Dagahaley, Kenya - KARAMBU, MURIUNGI PAMELA (My University, 2013)
The main objective of this study was to examine access to basic education for child refugees in the Dadaab refugee camps of Ifo, Hagadera and Dagahaley,Kenya. The study adopted a descriptive survey research design. The independent variables were teaching/learning resources, physical facilities and socio-cultural practices while the dependent variable was education. The target population comprised of primary school head teachers, teachers, pupils and parents. Stratified random sampling was used to sample schools to ensure proportionate distribution of schools within the camps. A total of 10 primary schools were selected using stratified random sampling. This formed 55.5% of the total population. From each selected school, the head teacher and 13 teachers were sampled for the study yielding 10 head teachers and 130 teachers. From each school 13 class 7 pupils were randomly sampled and this yielded 130 pupils. In addition to the above respondents, 20 parents were conveniently sampled and interviewed.The research instruments used were document analysis forms for head teachers, questionnaires for teachers and pupils and interview schedules for parents.A pilot study was done to establish the validity and reliability of the research instruments. The calculated reliability coefficient using spearman brown prophecy formula was 0.82.Data obtained was analyzed using descriptive statistics such as frequencies, percentages, tables, graphs and charts. Discussions of the findings established that in-school as well as out-of-school factors greatly hampered the access to basic education in the schools for refugee children. Out of school factors included such factors as lack of parental support, high levels of poverty, child labor and sociocultural factors which both affected the girl child more than the boy child. In-school factors included lack of resources, untrained teachers, inadequate physical facilities and lack of specialized equipment for learners with other disabilities.From the findings of the study the researcher recommended that since majority of the camp schools are registered with the Ministry of Education, the Directorate of Quality Assurance and Standards should carry out advisory in these schools.The implementing partners in the education programme should come up with incentives to motivate learners in order to maintain them in school after enrollment,the Government of Kenya through the Ministry of Education and the implementing partners should ensure provision of adequate teaching/learning resources as well as specialized equipment for learners with other disabilities in the camp schools. The education implementing partners should come up with strategies of reducing gender disparities in education by encouraging girls to remain in school and finally the school administration with the help of implementing partners should organise ways of ensuring adequate provision of physical facilities in the schools
Keywords: Education; Dadaab; Refugee